2014
DOI: 10.1186/1746-6148-10-s1-s2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective survey of veterinary practitioners’ primary assessment of equine colic: clinical features, diagnoses, and treatment of 120 cases of large colon impaction

Abstract: BackgroundLarge colon impactions are a common cause of colic in the horse. There are no scientific reports on the clinical presentation, diagnostic tests and treatments used in first opinion practice for large colon impaction cases. The aim of this study was to describe the presentation, diagnostic approach and treatment at the primary assessment of horses with large colon impactions.MethodsData were collected prospectively from veterinary practitioners on the primary assessment of equine colic cases over a 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
2
24
0
2
Order By: Relevance
“…These are non‐specific mild signs, which may be seen in normal horses, but are also potential signs of colic. They may be the only signs in less severe types of colic, such as large intestinal impactions , or early signs of other severe conditions, such as colitis or peritonitis. Again, this highlights potential issues around decision‐making for horses showing less severe or non‐specific signs of colic.…”
Section: Discussionmentioning
confidence: 99%
“…These are non‐specific mild signs, which may be seen in normal horses, but are also potential signs of colic. They may be the only signs in less severe types of colic, such as large intestinal impactions , or early signs of other severe conditions, such as colitis or peritonitis. Again, this highlights potential issues around decision‐making for horses showing less severe or non‐specific signs of colic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in period C (1999 -2000), heart rate was also found to be useful as a prognostic indicator. Heart rate has previously been identified as a factor in differentiating critical from non-critical colic cases (Jennings et al 2014, Curtis et al 2015 and has been found to predict mortality in colic cases (Puotunen-Reinert and Huskamp 1985, Orsini et al 1988, Reeves et al 1989, Furr et al 1995 There was a statistically significant difference in blood pH between survivors and non-survivors, and acidosis was associated with increased odds of death, although it is unclear whether this difference is clinically relevant, as mean values for both groups were within the reference range. The higher blood lactate concentration in non-survivors would likely…”
Section: Discussionmentioning
confidence: 99%
“…Ceftiofur sodium (Naxcel; Zoetis, Kalamazoo, MI 49007, USA), 1.1 mg/kg IM q 24 hr (Dumonceaux, Isaza, Koch, & Hunter, 2005) was given for seven days to prevent infection from a potential compromised bowel wall. Gastrointestinal sounds and heart rate are the most important primary measurements for distinguishing between simple and critical colic in horses (Jennings, Curtis, Burford, & Freeman, 2014). In our patient, the heart rate was difficult to auscultate and the auricular vein could not be easily assessed due to a previous injury to the ears.…”
mentioning
confidence: 74%